Democracy as an Elite Tool for Oppressing the Majority: A Case of Selected African Countries - Mohale Ernest Selelo; Magatane Tshwarelo Mashilo (Journal of Governance Risk Management Compliance and Sustainability, 2023)
This paper seeks to establish and investigate the incontrovertible scenarios that the people of Zimbabwe and Uganda experienced during the dawn of democracy. This paper argues that "democracy" is a system beneficial to the elites but unbearable and detrimental to the livelihoods of ordinary people in Zimbabwe and Uganda. The democratic breakthrough in these countries brought hope, confidence, and zest to the proletariats that their dire socio-economic conditions would be transformed for the better. But little did they know that their conditions would be exacerbated than ever before. The high levels of inequalities, poverty and unemployment in these countries continue to haunt the people. Unfortunately, this happens under the ambit of AU, which is tight-lipped to such conditions people are going through. Regrettably, it appears as if the ones who are in positions of leadership are fueling the abuse of democracy, wherein they abuse their power in government to orchestrate their illegitimate shenanigans. Subsequently, human rights are often violated and suppressed when the “mighty” officials want to influence the processes of democracy with a direct autocratic system. Despite the calls from the UN that human rights and democracy should be respected and adhered to, people continue to witness the violence and suppression of such principles under the ambit of democratic governments. This paper uses a qualitative research approach to analyze the scenarios of the abuse of democracy in these countries. This paper finds that the violation of freedom of expression, assembly, and freedom of association is prevalent in these countries. Therefore, the paper recommends that structures such as the AU should enforce their responsibilities to safeguard and protect the rights of the people as per democratic states.